Dual Trading in Futures Markets. - Fishman, Michael J; Longstaff, Francis A (Journal of Finance, 1992)
With dual trading, brokers trade both for their customers and for their own account. The authors study dual trading and find that customers who are less likely to be informed have higher expected profits with dual trading while customers who are more likely to be informed have higher expected profits without dual trading. They also examine the effects of frontrunning. The authors test the major empirical implications of their model. Consistent with the model, dual traders earn higher profits than nondual traders, and customers of dual-trading brokers do better than customers of nondual-trading brokers.